Exploring the Effectiveness of Google Workspace Tools in Facilitating Reflective Teaching Practice Among Indonesian Primary School Teachers - Dian Utami (Journal of Education and Teacher Development, 2025)
The growing integration of digital tools in education has encouraged primary school teachers to adopt more reflective teaching practices supported by technology. This study explores the effectiveness of Google Workspace in facilitating reflective practice among Indonesian primary school teachers. Employing a qualitative content analysis approach, the research draws upon secondary sources such as training modules, teacher-authored reflections, and digital media related to classroom experiences. The findings reveal that Google Docs and Google Forms are the most frequently used tools, accounting for 32.99% and 24.74% of occurrences, respectively. These tools are primarily used for individual reflection and data-based self-evaluation. In contrast, collaborative reflection through platforms like Google Meet and Jamboard appears less common. The study suggests that while Google Workspace effectively supports structured and text-based reflective activities, it remains underutilized in promoting dialogic or community-based reflection. Based on these findings, the paper recommends targeted professional development, greater emphasis on collaborative reflection using digital platforms, and the institutionalization of digital reflection as part of ongoing teacher development. In the digital era, Google Workspace presents promising potential as a pedagogical tool for fostering meaningful and sustainable reflective practices in primary education.